Field dodder life cycle and interaction with host plants - Sarić-Krsmanović, Marija M; Vrbnicanin, Sava P (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Field dodder is a parasitic plant that attaches to stems and leaves of broadleaf plants, including weeds, field crops, vegetables and ornamentals, across most agricultural regions of the world. Effective field dodder control is extremely difficult to achieve due to the nature of attachment and close association between the host and the parasite, which require a highly effective and selective herbicide to destroy the parasite without damaging its host. To establish a strategy for controlling parasite growth and restricting the spread of field dodder in crop fields, it is important to learn more about this weed, its life cycle and development.